Dewetting and transport property enhancement: antimonide crystals for high performance electronic devices. Issue 4 (21st March 2013) - Ebnalwaled, A. A.; Duffar, T.; Sylla, L.
Abstract The dewetting technique has been applied to the growth of InSb and GaSb polycrystals. After optimization of the set up and growth parameters, four samples, 88 mm in length and 11 mm in diameter, have been obtained. Their electrical properties were investigated in relation to the type of solidification (attached, dewetted and so on). In spite of the polycrystalline structure of these samples, room temperature Hall mobilities obtained for dewetted antimonide samples have shown the highest values obtained till now. These results indicate that dewetting can be used to produce InSb and GaSb with high mobility for device applications.